Computer-based Malay stuttering assessment system - Ooi, Chia Ai (2007)
Stuttering has attracted extensive research interests over the past decades. However, far less effort has been done on the computer-based stuttering assessment system. Stutterers respond in unique ways to different therapy techniques. The technique that works so dramatically for one stutterer does not necessarily work dramatically, or at all, for other stutterers. Stuttering is so variable and so highly individualized that, few would disagree, no one method works for all stutterers. Normally, 2 to 3 months are required to determine suitable techniques for each client. The effectiveness of each approach depends on the receptiveness of the client. This thesis explains the development of a computer-based Malay stuttering assessment system. The system assists Speech-Language Pathologist (SLP) in determining suitable therapy techniques for each client. The software was developed based on fluency shaping techniques used in fluency rehabilitation regimen. Digital Signal Processing techniques were implemented to analyze speech signals. The maximum magnitudes of the clients’ and the SLPs’ speech signals, corresponding to the Average Magnitude Profiles (AMPs), were determined and compared. The maximum magnitude was determined where a total of 15 neighbouring samples were summed to obtain a maximum value. Start location, end location, maximum magnitude and duration were compared between clients’ and SLPs’ AMPs to generate scoring, the computational analyses help SLP to determine suitable techniques in a faster way. The software has been developed using Microsoft Visual C++ 6.0 to run under Window XP. Three therapy techniques were introduced in the proposed computer-based method. These techniques consisted of Shadowing, Metronome and Delayed Auditory Feedback. Ten test subjects were selected from 6 primary schools located at Skudai. Measurements of percent syllables stuttered on test subjects were made by SLP from Hospital Sultanah Aminah. The experimental results showed that SLP agreed with the result analyses generated by the software.